Analisis Implementasi Manajemen Risiko Operasional terhadap Pelayanan dan Sumber Daya Manusia: Studi Kasus pada Bengkel Mandiri Auto Service Surabaya - Syarifka Satya Putri Zaen; Ajeng Tita Nawangsari (Indo Publishing, 2025)
This study aims to determine how Bengkel Mandiri Auto Service in Surabaya implements operational risk management in the areas of service and human resources (HR). Operational risks can have a negative impact on service quality and employee performance if not handled properly. This study was conducted using a qualitative approach with a case study method. Data was collected through direct observation, interviews with management and employees, and documentation. The results of the study indicate that the workshop has implemented operational risk management in a phased manner, starting from identifying risks, analyzing, evaluating, and addressing them. Common risks include customer complaints, service delays, and HR capability mismatches. However, there are still some challenges, such as a lack of regular training for employees and an underutilized customer satisfaction monitoring system. Therefore, this study recommends that the workshop strengthen its internal evaluation system and enhance HR capabilities to support more effective and sustainable operational risk management.